Application of the #Enzian classification for endometriosis on MRI: prospective evaluation of inter- and intraobserver agreement - Harth, Sebastian; Kaya, Hasan Emin; Zeppernick, Felix; Meinhold-Heerlein, Ivo; Keckstein, Jörg; Yildiz, Selcuk Murat; Nurkan, Emina; Krombach, Gabriele Anja; Roller, Fritz Christian (Frontiers in Medicine, 2023)
Objectives The purpose of this investigation was to evaluate the inter- and intraobserver variability of the updated #Enzian classification of endometriosis on MRI and to evaluate the influence of reader experience on interobserver concordance. Methods This was a prospective single-center study. All patients were included who received an MRI of the pelvis for evaluation of endometriosis between March and July 2023 and who have provided written informed consent. Images were reviewed independently for endometriosis by three radiologists, utilizing the MRI-applicable categories of the #Enzian classification. Two radiologists had experience in pelvic MRI and endometriosis imaging. One radiologist had no specific experience in pelvic MRI and received a one-hour briefing beforehand. Results Fifty consecutive patients (mean age, 34.9 years ±8.6 [standard deviation]) were prospectively evaluated. Interobserver agreement was excellent for diagnosis of deep infiltrating endometriosis (Fleiss’ kappa: 0.89; 95% CI 0.73–1.00; p < 0.001) and endometriomas (Fleiss’ kappa: 0.93; 95% CI 0.77–1.00; p < 0.001). For the experienced readers, interobserver agreement in the assessment of compartments A, B and C was excellent (κw ranging from 0.84; 95% CI 0.71–0.97; p < 0.001 to 0.89; 95% CI 0.82–0.97; p < 0.001). For the pairings of the experienced readers to the reader without specific experience in pelvic MRI, agreement was substantial to excellent (κw ranging from 0.64; 95% CI 0.44–0.85; p < 0.001 to 0.91; 95% CI 0.84–0.98; p < 0.001). Intraobserver variability was excellent for compartments A, B and C (κw ranging from 0.85; 95% CI 0.73–0.96; p < 0.001 to 0.95; 95% CI 0.89–1.00; p < 0.001). Conclusion With sufficient experience, the #Enzian classification enables the achievement of excellent inter- and intraobserver agreement in MRI-based diagnosis of deep infiltrating endometriosis and endometriomas.